LIPUS Responsive Dopamine-Modified PVDF Piezoelectric Nanofiber Membrane for Full-Thickness Skin Wound Healing - Zhang Z; Liu L; Wang H; Xie W; Zhai W; Wen L; Zhang B; Liu K; Zhang X; Liu S; Huang L; Li D; et al. (International Journal of Nanomedicine)
Zhiying Zhang,1,* Lijun Liu,1,* Huan Wang,2,* Wangni Xie,1 Wenhao Zhai,1 Linlin Wen,1 Boya Zhang,1 Kexuan Liu,1 Xue Zhang,1 Shuchen Liu,1 Lei Huang,1 Daowei Li,1 Yanmin Zhou1 1Jilin Provincial Key Laboratory of Tooth Development and Bone Remodeling, Hospital of Stomatology, Jilin University, Changchun, 130021, People’s Republic of China; 2State Key Laboratory of Rare Earth Resources Utilization and Laboratory of Chemical Biology, Changchun Institute of Applied Chemistry, Chinese Academy of Sciences, Changchun, 130022, People’s Republic of China*These authors contributed equally to this workCorrespondence: Daowei Li, Email jluldw@jlu.edu.cn Yanmin Zhou, Email Zhouym@jlu.edu.cnObjective: Large full-thickness skin wounds pose significant challenges, particularly in achieving scar-free healing and the regeneration of skin appendages. This study introduces a portable approach for promoting scarless healing and skin appendage regeneration by utilizing low-intensity pulsed ultrasound (LIPUS) activated piezoelectric electrospun membranes to modulate the local electrical environment.Methods: Dopamine-modified polyvinylidene fluoride (DA/PVDF) nanomembranes were fabricated via electrospinning, followed by piezoelectric characterization under varying LIPUS stimulation. Cell adhesion was examined using SEM and laser confocal microscopy to assess surface interactions. Cell proliferation and migration were further analyzed using the CCK-8 assay and Transwell migration assay, respectively. Finally, the effects of DA/PVDF membranes on full-thickness skin defect healing were tested in a mouse model. The healing process was documented with photographs, and functional skin regeneration was evaluated through histological analysis.Results: The DA/PVDF nanomembranes had an average diameter of 732 ± 232 nm and generated a voltage of 450 mV under LIPUS stimulation, a 1.28-fold increase compared to PVDF membranes alone. In vitro, LIPUS-activated membranes enhanced cell adhesion and proliferation, resulting in a 1.14-fold increase in cell growth over three days. The transwell migration assays showed 244.67 ± 7.85 migrated cells. In vivo, the DA/PVDF+LIPUS group exhibited significantly higher wound healing rates, with improved epidermal regeneration, collagen fiber deposition and remodeling, and enhanced blood vessel and skin appendage formation.Conclusion: DA modification enhances the piezoelectric properties of PVDF membranes, boosting cell adhesion and promoting dermal and vascular regeneration. LIPUS-generated mechanical waves effectively stimulate membrane deformation, producing a localized electrical microenvironment that mimics the natural bioelectric field of skin and accelerates functional wound healing. Keywords: piezoelectric materials, dopamine, low-intensity pulsed ultrasound, skin wound healing, skin appendage regeneration